The Deaf-blind and their rehabilitation services in India - P, Rama Mohan Babu; N, Rathna (Journal of All India Institute of Speech and Hearing, 1972)
A deaf-blind child is one whose sense of hearing is non-functional for the ordinary purposes of life with or without a hearing aid and whose vision is nonfunctional for the ordinary purposes of life with or without correcting glasses